2004
DOI: 10.1007/s00280-004-0883-1
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy for gastric cancer in Japan: global and Japanese perspectives

Abstract: Adjuvant therapy for gastric cancer after surgical resection has been under clinical investigation for decades. However, up until now, consistent and concrete evidence has not been generated either in Japan or other countries in favor of adjuvant therapy in terms of survival compared to surgery alone. Meta-analyses reported from Western countries have shown either no or borderline benefit for chemotherapy after surgical resection of gastric cancer. A recent trial showed significant benefit for chemoradiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
0
18
0
2
Order By: Relevance
“…This study demonstrated that the adjuvant UFT chemotherapy signifi cantly prolonged the overall survival of the patients. 28 In contrast to the NSAS-GC01 trial, the Japan Clinical Oncology Group (JCOG) 9206-2 trial could not show a survival benefi t of adjuvant chemotherapy with cisplatin plus 5-FU followed by UFT for resected serosalpositive (T3 and T4) gastric cancer. 29 The effi cacy of UFT was infl uenced by the status of enzymes involved in 5-FU metabolism such as thymidylate synthase (TS) and dihydropyrimidine dehydrogenase (DPD).…”
Section: Therapeutic Procedures Used To Treat Sgcmentioning
confidence: 98%
“…This study demonstrated that the adjuvant UFT chemotherapy signifi cantly prolonged the overall survival of the patients. 28 In contrast to the NSAS-GC01 trial, the Japan Clinical Oncology Group (JCOG) 9206-2 trial could not show a survival benefi t of adjuvant chemotherapy with cisplatin plus 5-FU followed by UFT for resected serosalpositive (T3 and T4) gastric cancer. 29 The effi cacy of UFT was infl uenced by the status of enzymes involved in 5-FU metabolism such as thymidylate synthase (TS) and dihydropyrimidine dehydrogenase (DPD).…”
Section: Therapeutic Procedures Used To Treat Sgcmentioning
confidence: 98%
“…50,51 This study failed to show a signifi cant survival benefi t of postoperative adjuvant chemotherapy with MF plus UFT for T1-2 gastric cancer, but it did show a trend in favor of the adjuvant chemotherapy Recent meta-analyses of RCTs of adjuvant chemotherapy conducted in Japan showed a small or borderline survival benefi t of postoperative adjuvant chemotherapy, especially UFT-containing chemotherapy, for resected gastric cancer. 53,54 More recently, a meta-analysis of centrally randomized adjuvant UFT (Table 5). In the meta-analysis, a total of 1503 patients were analyzed, and there proved to be a signifi cant survival benefi t for the postoperative adjuvant UFT treatment (HR = 0.70 [95% CI: 0.54-0.89] and P = 0.01).…”
Section: Gastric Cancermentioning
confidence: 99%
“…39 Therefore, it is generally accepted in Japan that surgery alone remains a standard therapy for respectable gastric cancer. 37,38 As UFT is an active and well-tolerated chemotherapeutic agent for gastric cancer, 47 a series of RCTs of adjuvant chemotherapy containing UFT for resected gastric cancer have been conducted by the Japan Clinical Oncology Group (JCOG) [48][49][50][51][52] and other cooperative study groups in Japan 37 (Table 2). In the JCOG-8801 trial, a total of 579 patients with curatively resected gastric cancer (T1 with nodal metastasis or T2 disease) were randomly assigned to the surgery-alone group or surgery followed by the chemotherapy group; chemotherapy consisted of intravenous chemotherapy (mitomycin C [MMC] plus 5-FU, MF) followed by oral UFT administration.…”
Section: Gastric Cancermentioning
confidence: 99%
“…Significant geographic variation exists, with high-risk areas such as Japan, Eastern Asia, and Central and South America (Terry et al, 2002;Sakamoto et al, 2004). The incidence is relatively low in the United States; however, gastric cancer is a significant cause of morbidity and mortality, with 23 000 cases per year, resulting in 12 000 annual deaths (Jemal et al, 2004).…”
mentioning
confidence: 99%